Islamic Pop-Up Book Development to Improve The Morals of Children Aged 5-6 Years - Munawaroh Munawaroh; Dian Tri Utami; Alucyana Alucyana; Yenni Yunita (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Abilities that must be developed in children's potential, namely education about good and bad behavior that is the basis of children's social life. Early childhood moral development is very important to form an attitude of discipline, responsibility, politeness, and the ability to respect others. However, the moral development of children aged 5-6 years is still not optimal, characterized by behavior of teasing each other, lack of discipline, breaking rules, and lack of respect for friends and teachers. In addition, the use of learning media in kindergarten is still limited and does not utilize interactive visual media that is interesting for children. This study aims to determine the feasibility and effectiveness of the development of Islamic Pop-Up Book media in improving the morale of children aged 5-6 years. This study used the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, and questionnaire validation. Product validation was carried out by two media expert validators and material experts as well as five certified kindergarten educators. The results showed that the Islamic Pop-Up Book media received a very good rating, with a validation percentage of 93.06% from validator I, 91.67% from validator II, and 97.73% from educators. This media effectively provides an engaging learning experience through visualization of Islamic stories and instills moral values ​​in children's daily lives.